(untitled) (Statistics, Optimization & Information Computing, 2025)
lIn this study, we suggest the weighted Exp-G (WExp-G) continuous distributions as a novel class of continuous distributions with an additional shape parameter. Then we study the basic mathematical properties. We study Lindley and XGamma special cases. This model is exible for modelling right skew data sets. The hazard rate of this model is decraesing, increasing and bathtub shape. By performing a simulation analysis, we compared different common methods of estimation. Finally we analyzed and used lifetime, failure time and stress real data sets to illustrate the purposes. This model is perfrom better than other two-parameter distribution.